2012
DOI: 10.4103/2278-0203.99760
|View full text |Cite
|
Sign up to set email alerts
|

Mesiodistal tooth width and tooth size discrepancies of Yemeni Arabians: A pilot study

Abstract: Objectives:The aims of this study were to determine the mean mesiodistal tooth size width and Bolton's anterior and overall ratios, find any possible sex differences, and study the frequency of tooth size discrepancies among Yemeni population and if there is a difference in tooth size between the right and left sides.Materials and Methods:176 subjects aged 13–25 years (94 females and 82 males) with different types of malocclusions (94 Angle Class I, 37 Class II division 1, 36 Class II division 2, and 9 Class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
(60 reference statements)
5
22
0
1
Order By: Relevance
“…According to the present study, no statistically significant differences were found between genders in anterior or overall Bolton’s ratio for each malocclusion group. These findings are in the line with previous researches on several other populations ( 13 – 15 , 19 24 ). On the other hand, some other investigations showed statistically significant differences between genders in the overall ratio for the malocclusion groups ( 23 , 25 ) and in the anterior ratio ( 23 , 26 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to the present study, no statistically significant differences were found between genders in anterior or overall Bolton’s ratio for each malocclusion group. These findings are in the line with previous researches on several other populations ( 13 – 15 , 19 24 ). On the other hand, some other investigations showed statistically significant differences between genders in the overall ratio for the malocclusion groups ( 23 , 25 ) and in the anterior ratio ( 23 , 26 ).…”
Section: Discussionsupporting
confidence: 93%
“…Besides that, sexual dimorphism of the teeth dimension is related to humanoid sex genes and hormones and is influenced by their imbalance ( 7 9 ). Furthermore, teeth size have been studied worldwide in order to compare various populations that have specific characteristics and to determine the patterns of variability between different teeth, associations within and between dental arches ( 1 , 2 , 5 , 6 , 9 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tooth measurement was conducted on study models which offers a significant improvement on direct intra-oral tooth measurement and allow remeasurement when required. [3334] Racial variations in MD tooth width have been noted by previous researchers[51113243536] and therefore variations in MD tooth width are likely to be population-specific. Moreover, males are consistently found to have larger teeth than females.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies have reported differences in the dentition between past and present in Japanese populations [1][2][3]8) . Few studies have compared differences in the sizes of the deciduous teeth and dental arch between past and present in such a population, however.…”
Section: Introductionmentioning
confidence: 99%